Cytokine crowdsourcing: multicellular production of TH17‐associated cytokines. Issue 3 (29th December 2014) - Busman‐Sahay, Kathleen O.; Walrath, Travis; Huber, Samuel; O'Connor, William
Abstract : Review of critical non‐TH17 sources of IL‐17A and associated cytokines during inflammation in mucosal tissues, with a focus on leukocytes of the gastrointestinal tract. Abstract : In the 2 decades since its discovery, IL‐17A has become appreciated for mounting robust, protective responses against bacterial and fungal pathogens. When improperly regulated, however, IL‐17A can play a profoundly pathogenic role in perpetuating inflammation and has been linked to a wide variety of debilitating diseases. IL‐17A is often present in a composite milieu that includes cytokines produced by TH 17 cells (i.e., IL‐17F, IL‐21, IL‐22, and IL‐26) or associated with other T cell lineages (e.g., IFN‐ γ ). These combinatorial effects add mechanistic complexity and more importantly, contribute differentially to disease outcome. Whereas TH 17 cells are among the best‐understood cell types that secrete IL‐17A, they are frequently neither the earliest nor dominant producers. Indeed, non‐TH 17 cell sources of IL‐17A can dramatically alter the course and severity of inflammatory episodes. The dissection of the temporal regulation of TH 17‐associated cytokines and the resulting net signaling outcomes will be critical toward understanding the increasingly intricate role of IL‐17A and TH 17‐associated cytokines in disease, informing our therapeutic decisions. Herein, we discuss important non‐TH 17 cell sources of IL‐17A and other TH 17‐associated cytokines relevant to inflammatory events in mucosal tissues.